Recognizing states international society and the establishment of new states since 1776 - Fabry, Mikulas (Oxford : Oxford University Press, 2010)
This text charts the historical practice of recognizing states since the late 18th century and examines a central question raised by the new, lingering demands for statehood in different parts of the world: who qualifies for international recognition as a sovereign, independent state?
Description based on print version record.
Includes bibliographical references and index.
Keywords: State succession -- History; Recognition (International law) -- History; Legitimacy of governments; Self-determination, National